Luminescence properties of Ca₃Ga₂Ge₄O₁₄ crystals - Kostyk, L.; Tsvetkova, O.; Stryganyuk, G. (Functional Materials, 2008)
The spectral and kinetic luminescence characteristics of undoped Ca₃Ga₂Ge₄O₁₄ single crystals have been studied using synchrotron irradiation with 4-30 eV energy, X-ray and optical irradiation (N₂ laser) in 10-300 K temperature range. It is established that the undoped crystals show an intrinsic luminescence consisting of three elementary emission bands peaked at 355, 400, and near 500 nm. The UV emission bands (355 and 400 nm) are effectively excited in exciton absorption and band-to-band regions while the 500 nm emission can be excited in the crystal transparency region. Possible nature of intrinsic luminescence bands in Ca₃Ga₂Ge₄O₁₄ crystals is discussed. Досліджено спектрально-люмінесцентні та кінетичні характеристики неактивованих
монокристалів Ca₃Ga₂Ge₄O₁₄ при збудженні синхротронним випромінюванням з
енергією 4-30 еВ, рентгенівськими променями та оптичним випромінюванням (N₂ -
лазер) у температурному діапазоні 10-300 К. Показано, що кристали, які досліджуються,
характеризуються власною люмінесценцією, яка складається з трьох елементарних
смуг з максимумами при 355, 400 та 500 нм. Смуги 355, 400 нм ефективно
збуджуються в області екситонного поглинання та зона-зонних переходів, а свічення
500 нм в області прозорості кристала. Обговорюється можлива природа смуг власного
свічення у кристалах Ca₃Ga₂Ge₄O₁₄. Исследованы спектрально-люминесцентные и кинетические характеристики неактивированных монокристаллов Ca₃Ga₂Ge₄O₁₄ при возбуждении синхротронным излучением с энергией 4-30 эВ, рентгеновскими лучами и оптическим излучением (N₂ -лазер) в температурном диапазоне 10-300 К. Показано, что исследованные кристаллы характеризуются собственной люминесценцией, которая состоит из трех элементарных полос с максимумами при 355, 400 и 500 нм. Полосы 355, 400 нм эффективно возбуждаются в области экситонного поглощения и зона-зонных переходов, а свечение 500 нм в области прозрачности кристалла. Обсуждается возможная природа полос собственного свечения в кристаллах Ca₃Ga₂Ge₄O₁₄.